Posterior fossa surgery and CerebroSpinal Fluid Leak: Review of How to Prevent and Treatment: https://doi.org/10.59156/revista.v37i03.446 - Asis, Santiago; Sciarra, Mariano; Toscano, Maximiliano; Montivero, Agustin Jorge; cabanillas, juan manuel jesus; De Battista, Juan Carlos (Revista Argentina de Neurocirugía, 2023)
Background: Cerebrospinal fluid (CSF) leakage is a frequent complication of posterior fossa surgery. Objectives: To study a bibliographic review of fistula prevention through different dural defect repair techniques and analyze risk factors in the management of postoperative fistula. Methods: A bibliographic search was performed using Medline, Cochrane and Embase. Results: 413 studies were considered at the beginning, 367 were discarded and 46 were selected. Conclusion: To conclude that there is not an ideal dural sealant. We recommend the use of autografts due to their relative ease, low cost and high effectivity, particularly pericranium, combined with dural sealants like Duragen® or DuraSeal®. In the suboccipital approach cervical fascia is another option. If not technically possible the use of an autologous graft, collagen matrix have higher efficiency combined with Polietilenglicol Sealants. If CSF leakage appears, for the management is necessary the use of conservative actions associated with External Lumbar Drainage (ELD) as quickly as possible because it increases efficacy.